'Critical friends': exploring arm's length actor relationships to local government in education. Issue 6 (1st November 2016) - Exley, Sonia
Abstract: Discussions charting the changing role of local government in education have often focused extensively on 'concrete' policy changes over time, but have provided less detail on the contribution to changing power relations of less tangible shifts. Drawing on Foucauldian notions of discourse and governmentality, in this paper, detailed rationalities of local third-sector and other 'arm's length' actors in English education are explored, with a focus on their relationship to local authority (LA) school admissions teams. The paper aims to provide deeper understanding of tactical struggles for authority which happen within competitive local sociopolitical spaces. Data is utilised from a study of 'Choice Advice' (CA) in 10 LAs, within a background context where arm's length agents deployed to deliver CA have been co-opted into central government marketisation regimes, but local state planning of schooling is arguably more equitable for vulnerable families than are logics advancing a marketisation of education. The research reveals: (1) discourses valourising 'independence' and 'distance' from local state 'agendas'; (2) discourses separating the interests of 'parents' and 'schools', with LAs positioned as representing the latter; (3) dehumanising representations of LA officers as 'faceless', obstructive and requiring regulation from 'critical friends'.